2019
DOI: 10.3390/catal9030228
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Mono- and Dithiols of Tetraethylene Glycol and Poly(ethylene glycol)s via Enzyme Catalysis

Abstract: This paper investigates the transesterification of methyl 3-mercaptopropionate (MP-SH) with tetraethylene glycol (TEG) and poly(ethylene glycol)s (PEG)s catalyzed by Candida antarctica Lipase B (CALB) without the use of solvent (in bulk). The progress of the reactions was monitored by 1H-NMR spectroscopy. We found that the reactions proceeded in a step-wise manner, first producing monothiols. TEG-monothiol was obtained in 15 min, while conversion to dithiol took 8 h. Monothiols from PEGs with Mn = 1000 and 205… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Alternatively, the triplets adjacent to the left (δ = 3.82 ppm) and right (δ = 3.47 ppm) of the major peaks have also been assigned to protons b and d . Such assignments , are, however, incorrect.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, the triplets adjacent to the left (δ = 3.82 ppm) and right (δ = 3.47 ppm) of the major peaks have also been assigned to protons b and d . Such assignments , are, however, incorrect.…”
Section: Resultsmentioning
confidence: 99%
“…The most common practice is thus to characterize PEG functionalization with small anchoring moieties by 1 H NMR. Unfortunately, many published 1 H NMR of functionalized PEGs are incorrectly analyzed without taking into consideration the 13 C– 1 H coupling, which leads to erroneous peak assignments and incorrect quantification of PEG functionalization. Herein, we walk the reader through correct interpretation of 1 H NMR spectra of functionalized PEG.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the NCs showed no tendency to redisperse in aqueous MPA (pH 6) at either set of conditions, perhaps because van der Waals attraction between the MPAcapped NCs prevents the NC precipitates from dissolving. While MPA failed to redisperse the NCs, the longer-chain thiol acids MUDA and MHDA dissolved the NC precipitates to give pink-white emulsions that, upon filtering to remove the 105 After ozonation, the αand β-methylene triplets shift downfield while the ether backbone peak area decreases by ∼15%. The postozonation spectrum is assigned to a mixture of hexa(ethylene glycol) disulfonic acid (HEGDS) and its breakdown products.…”
Section: At Intermediate [Hegdt]/[nc] Values Aggregation Is Fast (1−2...mentioning
confidence: 99%
“…(a) 1 H NMR spectra of a 10 mM solution of HEGDT in pure D 2 O before and after 5 min of ozonation. The HEGDT spectrum shows the expected α-methylene triplet at 2.73 ppm (labeled a), β-methylene triplet at 3.67 ppm (labeled b), and oligo ethylene glycol backbone at 3.70 ppm (labeled c−f), in agreement with the literature 105. After ozonation, the αand β-methylene triplets shift downfield while the ether backbone peak area decreases by ∼15%.…”
mentioning
confidence: 99%
“…Among the research articles presented in this issue, there is a set of studies on enzyme catalysis, which was a powerful tool to effectively synthesize various target products. In more detail, Mulay et al investigated Candida antarctica Lipase B-catalyzed transesterification of methyl 3-mercaptopropionate with tetraethylene glycol (TEG) and poly(ethylene glycol)s (PEG)s to synthesize thiol-functionalized TEGs and TEGs without use of solvent [1]. Joo et al reported the biosynthesis of ω-hydroxydodecanoic acid via whole-cell biotransformations using a novel monooxygenase CYP153AL.m from Limnobacter sp.…”
mentioning
confidence: 99%